Assessment and optimization of the power performance of twin vertical axis wind turbines via numerical simulations. (March 2020) - Peng, H.Y.; Han, Z.D.; Liu, H.J.; Lin, K.; Lam, H.F.
Abstract: The power performance of twin vertical axis wind turbines (VAWTs) is believed to surpass that of their individual counterparts. In this study, the power performance of twin VAWTs was investigated via computational fluid dynamics (CFD) simulations by changing their configuration parameters, including the airfoil section (NACA), solidity ratio ( σ ), pitch angle ( β ), rotational direction ( φ ), and turbine spacing ( S / D ). The CFD model was validated against wind tunnel test data from the literature. An L16 (4 5 ) orthogonal table was adopted to optimize the power performance using the Taguchi method. The rated power coefficient ( C P ) and rated tip speed ratio (TSR) were calculated for the 16 cases in the table. The extent of impact of the five parameters on the rated TSR ranked as σ ˃ β ˃ NACA ˃ φ ˃ S / D . In comparison, the extent of impact of these parameters on C P ranked as β ˃ S / D ˃ σ ˃ NACA ˃ φ . The optimal and worst configurations of the twin VAWTs were determined and their C P values increased by 13% and 8%, respectively, from that of their standalone counterparts. Moreover, the rated TSRs of the twin VAWTs differed from those of their standalone counterparts. Highlights: CP assessment of twin VAWTs via analyzing structural and layout parameters . Twin configurations of VAWTs demonstrate excellent power performance . Ranking of affecting factors on λRated is attained as σ ˃ β ˃ NACA ˃ φ ˃ S / D . Parameters exerting impacts on CP are ranked as β ˃ S / D ˃ σ ˃ NACA ˃ φ . Increases of 13% and 8% in CP in optimal and worst configurations, respectively.